In Search Of. . . Research Methods Used in Information Science - Bernhard, Paulette; Lambert, Louise (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This article provides, first, a review of indicators of "research articles" as found in five different kinds of studies (content analysis of core journals and of specific journals, review of doctoral thesis, analysis of secondary journals, analysis of other sources), and second, the identification of the research methods listed in those studies, as well as in eleven textbooks about research and research methods.